Field investigation of the fetch effect and essential conditions for saturated sand flow. Issue 9 (21st April 2022) - Zhang, Chunlai; Wang, Xuesong; Zou, Xueyong; Shen, Yaping; Wang, Rende; Wang, Hongtao
Abstract: Several models of classical aeolian sand transport mechanism have been developed to predict the rate of sand transport. However, the values predicted through modeling almost always display large and significant differences from the measured values. The reason for such discrepancies is not fully understood. By studying the effects of wind velocities and fetch lengths on the C values in the model proposed by Lettau and Lettau in 1978, we found that the saturation level of the measured sand flow can significantly affect the accuracy of the predicted value. To solve this problem, we introduced an index ( δ ) to represent the saturation level. The closer the δ value is to 1, the greater the chance that the sand flow is saturated. This new approach only requires measurement of the saturated sand flow data to verify the robustness of the aeolian sand transport model, a step that has been neglected by previous researchers. Our results suggest that the value of C  = 6.7 proposed in the Lettau and Lettau model is sound and reliable if the sand flow is saturated. We proposed the conditions required for the sand flow to reach saturation and generated an equation to predict the sand transport saturation length ( L sat ). Accordingly, we estimated L sat to be approximately 92 m when u *  = 0.47 m s −1 for the studied sand surface, which is also the minimum wind shear velocity at which the sand flow can potentially reach saturation. Abstract : Our results suggest that the value of C  = 6.7 proposed by Lettau and Lettau in 1978 is sound and reliable if sand flow is saturated.